Immune Modulatory Effects of Human Chorionic Gonadotropin on Dendritic Cells Supporting Fetal Survival in Murine Pregnancy - Dauven, Dominique; Ehrentraut, Stefanie; Langwisch, Stefanie; Zenclussen, Ana Claudia; Schumacher, Anne (Frontiers in Endocrinology, 2016)
Dendritic cells (DCs) are critically involved in the determination of immunity versus tolerance. Hence, DCs are key regulators of immune responses either favoring or disfavoring fetal survival. Several factors were proposed to modulate DC phenotype and function during preg-nancy. Here, we studied whether the pregnancy hormone human Chorionic Gonadotropin (hCG) is involved in DC regulation. In vitro, bone-marrow-derived DCs (BMDCs) were stimulated in the presence or absence of urine-purified (uhCG) or recombinant hCG (rhCG) preparations. Subsequently, BMDC matu-ration was assessed. Cytokine secretion of activated BMDCs and their capability to enforce TH1, TH2, TH17 or Treg cell differentiation was determined after rhCG treatment. Moreover, the in vivo potential of hCG-modulated BMDCs to influence pregnancy outcome, Treg cell number and local cytokine expression was evaluated after adoptive transfer in a murine abor-tion-prone model before and after conception. Both hCG preparations impaired the maturation process of BMDCs. rhCG treatment did nei-ther alter cytokine secretion by BMDCs nor their ability to drive TH1, TH2 or TH17 differen-tiation. rhCG-treated BMDCs augmented the number of Treg cells within the T cell popula-tion. Adoptive transfer of rhCG-treated BMDCs after conception did not influence pregnancy outcome. However, transfer of hCG-treated BMDCs prior to mating had a protective effect on pregnancy. This positive effect was accompanied by increased Treg cell numbers and decidual IL-10 and TGF-β expression. Our results unveil the importance of hCG in retaining DCs in a tolerogenic state, thereby promoting Treg cell increment and supporting fetal survival.